Pomegranate juice supports therapeutic –treatment of atorvastatin against maternal hypercholesterolemia induced retinopathy of rat offspring. Issue 1 (1st January 2021) - EL-Sayyad, Hassan IH; El-Gallil, Hebattallah A Abd; El-Ghawet, Heba A
ABSTRACT: Dietary consumption of processed high fat diet led to the development of metabolic diseases. This study aimed to demonstrate the retinopathy in a rat offspring maternally fed on high cholesterol and the improvement of pomegranate juice (PJ) administration and atorvastatin as potential treatment. Eighty pregnant Wistar albino rats were categorized into eight groups (n = 10); the control, PJ supplementation [0.4 m L (20%)]; atorvastatin-treatment (10 mg/kg); and hypercholesterolemia (fed on 3% cholesterol for 6 weeks prior to conception, during pregnancy and lactation period. Retinas of 21-day-old rat offspring were investigated. Offspring maternally fed on a hypercholesterolemic diet exhibited internal retinal hemorrhage at the interphase between the pigment epithelium and photoreceptors leading to retinal detachment. In addition, widespread of degenerated stacked membrane of the photoreceptor outer segment and the neovascularization within the nuclear layers were observed. Offspring retina of a hypercholesterolemic mother exhibited a significant depletion of assayed neurotransmitters coinciding with a significant increase of the vacuolar endothelial growth factor apoptotic markers expressing pressing damaging of retinal cells. Co-administration of pomegranate juice to hypercholesterolemic mother rats treated with atorvastatin significantly improved the retinal structure and the assayed biochemical markers of offspring than that with atorvastatin-treatment. In conclusion, PJ showed a potent antiapoptotic and ant- angiogenesis activity and improved the histocytological pictures of rat offspring maternally subjected to hypercholesterolemia. Graphical Abstract: uf0001